Beading with filigree : beautiful jewelry, simple techniques - "Deis, cynthia" (Lark Books: New York, 2008)
Learn how to shape filigree components and alter their finish. Discover special techniques for combining the beads with the filigree. Release your creativity on projects packed with high-end style. The Dinner at Eight Necklace weds diamond-shaped filigree connectors with sparkly crystal beads. Whimsical Whirlwind Earrings feature painted filigree and silk ribbon that provide a surprising pop of color. Every piece is gorgeous!